Alcohol‐Related Consequences Among Intercollegiate Student Athletes: The Role of Drinking Motives. Issue 1 (7th April 2013) - Doumas, Diana M.
<x xml:space="preserve">Abstract</x> This study examined drinking motives as predictors of alcohol‐related consequences among student athletes and nonathletes. Results indicated that the highest level of alcohol‐related consequences was reported by student athletes with high levels of both coping and conformity motives.